Serum Biochemical Profile In Normally Calved and Retained Foetal Membranes Crossbred Cows - Rokde, K.; Kumar, S.; Mahour, S.S.; Nema, S.P.; Aich, R.; Solanki, Tamanna H.; Bhardwaz, A. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Serum biochemical profile revealed that the serum calcium, inorganic phosphorus, total protein and serum glucose in cross-bred cows were significantly (P<0.05) lower after 12 hrs post-partum and 7th day post-partum in cows having RFM as compared to normally calved cows. Lower levels of serum calcium, inorganic phosphorus, total protein and glucose may responsible for retention of foetal membranes.